2018
DOI: 10.24193/csq.22.2
|View full text |Cite
|
Sign up to set email alerts
|

West Africa: From Peacekeeping to Peace Enforcement. ECOWAS and the Regulations of Regional Security

Abstract: Abstract. The ECOWAS principle of non-interference in the internal affairs of member states included in its Charter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This study adopts a documentary research method to generate the information necessary to investigate fake news spread in Nigeria and its outcome, motivations for fake news sharing among Nigerians and fake news awareness among Nigerians. It has been shown that "the use of documentary research method requires careful and systematic study and analysis of documented sources based on written texts, visuals, and pictorial data which may be based on secondary data" (Agbo et al, 2018). Documentary research entails sourcing materials from documented facts or evidence, through a careful synthesis of data from available and accessible documents.…”
Section: Methodsmentioning
confidence: 99%
“…This study adopts a documentary research method to generate the information necessary to investigate fake news spread in Nigeria and its outcome, motivations for fake news sharing among Nigerians and fake news awareness among Nigerians. It has been shown that "the use of documentary research method requires careful and systematic study and analysis of documented sources based on written texts, visuals, and pictorial data which may be based on secondary data" (Agbo et al, 2018). Documentary research entails sourcing materials from documented facts or evidence, through a careful synthesis of data from available and accessible documents.…”
Section: Methodsmentioning
confidence: 99%
“…According to Payne and Payne, cited in Ahmed (2010), documentary methods are utilized for investigating and categorizing written documents. Agbo, Lenshie, & Boye (2018) expound that "The use of documentary research method requires careful and systematic study and analysis of documented sources based on written texts, visuals, and pictorial data which may be based on secondary data". Bailey (1994), cited in Ahmed (2010), says the documentary research method entails the analysis of documents that contain information about the phenomenon that one wishes to study.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the Nigerian military in peacekeeping operations across Africa and beyond has received global applause (Agbo et al, 2018; Nwangwu et al, 2019). The applause arising from Nigeria’s stellar military operations is attributed to its national security architecture.…”
Section: National Security Architecture Boko Haram Insurgency and Cou...mentioning
confidence: 99%